STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN SISWA DI SDN 11 SA’DAN - Lamba, Muriani; Padallingan, Yohanis; Salu, Benyamin (Al-mujahidah, 2025)
This study aims to examine the leadership strategies of the school principal in improving student discipline at SDN 11 Sa'dan. The issues faced include student characteristics that make it difficult for them to focus during lessons, as well as external factors such as the distance from students' homes to the school. This research uses a qualitative approach with a descriptive method, involving in-depth interviews, observations, and documentation. The results indicate that the principal applies several key strategies, including the development of school rules involving all school elements, regular supervision of students, a discipline development program that includes rewards and sanctions, and role modeling by the principal and teachers. Furthermore, extracurricular activities are also part of the strategy to build a culture of discipline. Despite challenges such as internal and external factors affecting student discipline, the policies implemented have had a positive impact on the discipline culture at SDN 11 Sa'dan